Self-deleting retrovirus vectors for gene therapy. - Russ, A P (1996)
A new generation of retrovirus vectors for gene therapy has been developed. The vectors have the ability to excise themselves after inserting a gene into the genome, thereby avoiding problems encountered with conventional retrovirus vectors, such as recombination with helper viruses or transcriptional repression of transduced genes. The strategy exploited (i) the natural life cycle of retroviruses, involving duplication of terminal control regions U5 and U3 to generate long terminal repeats (LTRs) and (ii) the ability of the P1 phage site-specific recombinase (Cre) to excise any sequences positioned between two loxP target sequences from the mammalian genome. Thus, an independently expressed selectable marker gene flanked by a loxP target sequence was cloned into the U3 region of a Moloney murine leukemia virus vector. A separate cassette expressing the Cre recombinase was inserted between the LTRs into the body of the virus. LTR-mediated duplication placed vector sequences, including Cre, between loxP sites in the integrated provirus. This enabled Cre to excise from the provirus most of the viral and nonviral sequences unrelated to transcription of the U3 gene.